Strange animals of Australia : koalas and kangaroos - Eugene, Toni.; National Geographic Society (U.S.) ([Washington, D.C.] : National Geographic Society, 1981)
Describes the characteristics and behavior of different kinds of Australian mammals, birds, and reptiles.
Keywords: Zoology -- Australia -- Juvenile literature; Zoology -- Australia; Australia